IMPROVING EFFICIENCY BY APPLYING INNOVATIONS IN THE LIVESTOCK SECTOR IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2024)
The article presents the ways to increase productivity by applying innovations in livestock farming. Animal husbandry is one of the leading sectors of agriculture in Uzbekistan. Meat, milk and egg products of the population provide industry with leather, wool and other raw materials. At present, when market relations are being formed, providing the population of the Republic with high-quality, ecologically clean and cheap livestock products is one of the important tasks. There are many branches of animal husbandry, such as cattle breeding, sheep breeding, poultry breeding, sheep breeding, fishing, and beekeeping. Therefore, the main tasks of the development of these industries are to establish a solid feed base, to continuously provide livestock with various servitamin, protein-rich, nutritious feeds throughout the year, to properly organize breeding-selection work, from advanced work experiences and achievements in science. effective use, new techniques that save costs, increasing the level of mechanization and automation of production processes as a result of the introduction of innovative and effective technologies, the widespread introduction of modern advanced technologies into practice and the specialization of farms in the formed production, and other factors were taken into account. Test examples are provided.